KEMATIAN SEBAGAI INSTRUMEN KEKUASAAN DALAM NOVEL MY SISTER’S KEEPER KARYA JODI PICOULT - Tomi Arianto (Universitas Putera Batam, 2017)
My Sister’s Keeper by Jodi Picoult is a novel which explores the phenomenon of American modern society in facing the death. The problem issue was the advancing attitude of American modern society toward the position of death as a threat which is also being denied, consequently labeled as Forbidden Death. Picoult explored the issue of Accute Promieleokosit Leucemia (APL) patient followed by the designed baby. There is a production of discourse and the utilization of the power behind the forbidden death discourse. This research uses the genealogical approach and discursive formations to find mechanisms of power in the novel. The result of the study depicted that the Forbidden Death on the novel was considered as the formation of discursive practice. Then there is also the utilization of power behind the discourse of death. Lastly, power requires a complex strategy and mechanism to legitimize the power of them through; bio-power, normalization, resistance and negotiations.